Medieval Indian history and architecture - Nath, R. (New Delhi : APH Pub. Corp., 1995)
Collection of papers.
Includes passages in Persian and Sanskrit.
Includes bibliographical references and index.
Keywords: India -- History -- 1000-1765.; Architecture, Medieval -- India; Architecture, Mogul -- India